Optimum conditions of keratinase production from Bacillus licheniformis - Hatif Sabri, Sara; Borhan Aldeen, Sanaa (Iraqi Journal of Science, 2023)
Forty isolates of Bacillus spp. were isolated from fifty samples including different source of soil to detect the ability to produce keratinase enzyme in liquid state fermentation, Bacillus (Bs13)was the highest keratinase producer , it was identified as a strain of Bacillus licheniformis. The optimum conditions for keratinase productions were in a media contains keratin 4% (hooves) as a carbon and nitrogen and energy sources, peptone 1% as a secondary nitrogen source with pH 8 , inculums size 1%, and incubated at 37Co for 24 hrs.